History of the museums, the mediators and scientific education - Brigitte Zana (JCOM: Journal of Science Communication, 2005)
Before analysing the role of the mediators in relation to scientific education, I deem it important to provide a short overview on how scientific museums evolved from the early curiosity cabinets to the modern web cast. Although the term “museum” is no longer adapted to the new structures employed for the diffusion of scientific and technical culture, the evolution of the means of presentation has indeed led to several forms of human mediation. This is of course the main topic we are going to take into consideration today, as it is an important element for the impact our exhibitions may have on the public. Decisions and choices vary from structure to structure for reasons that are sometimes justifiable but that are more often than not economic in nature, since wages, which are in any case very high no matter which country plays host, come to bear heavily especially on the budget of small and medium-sized structures.